Housing organization in a rural geographical setting - Aronés Cisneros, Angel Alcides (2021)
Abstract The objective was to analyze the organization of the houses in a rural geographical area from the spatial analysis in relation to the location and organizational characteristics in the Andes of Peru, the data were obtained from direct interviews with the families, supported by the systems geographic information through the processing of satellite images that allowed the development of thematic maps for analysis and interpretation. The conclusion in relation to the location of the houses 44% of them are located between 200 to 400 meters away from a water source; while in the organizational characteristic they are very common aspects, three rooms, the calamine ceiling and the construction of the adobe walls.